"WHAT WOULD HAPPEN IF A SHELL LANDED HERE NOW"? CORPOREAL VIOLENCE IN SEAN O'CASEY'S THE PLOUGH AND THE STARS AND THE SILVER TASSIE - Rosa, Ketlyn Mara (Revista X, 2020)
This article deals with the corporeal consequences of violence in two selected works of the Irish playwright Sean O’Casey, The Plough and the Stars (1926) and The Silver Tassie (1928). By focusing on the concepts of analysis of violence brought forth by Sarah Cole, the acts of bodily destruction in O’Casey’s works can be understood as portraying enchanted and disenchanted facets. The damage done to the human body is represented in complex ways in both plays as they demonstrate an intentional mixture of these two types of violence. Enchanted violence is perceived with the glorification of sacrifice while the physical consequences of destruction are hidden from sight whereas disenchanted violence insists on pointing out the hurt body, the grotesque side of pain that debunks any sense of heroism from battle. By analyzing passages from the plays in which physical violence becomes the focal point, the historical contexts of each play, the Easter Rising of 1916 and the First World War, are enlightened in a way that puts the body of the participants and their vivid experiences on the forefront, enhancing the sense of wastefulness and loss caused by armed conflicts.